Esearch of process water of a thermal power plant - Ospanova, D.; Nussupbekov, B.; Kutum, B.; Oshanov, Y. (Eastern-European Journal of Enterprise Technologies, 2 (6 (122)), 53–61., 2023)
The article is devoted to the study of technical water used in thermal power plants. One of the devices of thermoelectric plant are heat exchangers, heat exchangers consist of pipes of different diameters. Heat exchangers used in production plants are made of carbon steel, suitable for high temperatures (up to 565 °C). At the same time inside the heat exchangers used for a certain period of time, a scale is formed in the form of a solid sediment, which reduces the thermal efficiency of heat carriers. Therefore, in this paper, the object of research are the heat transfer fluids of industrial heat exchangers, namely feed and process water. In order to obtain feed water at industrial thermal power plants, special water treatment processes are carried out. That is, its main purpose is to prevent the formation of solid deposits in heat exchangers. The studied water samples were taken directly from the thermal power plant from different stages of water treatment, i. e. raw water entering the chemical shop, treated water entering the deaerator, feed water entering the boiler. As a result of the study, water samples related to the formation of scale on the surfaces of heat exchangers, i. e. dosed amounts, elemental composition and particles were studied. During the study, hourly, daily and monthly dosages of reagents were determined. In addition, the elemental compositions of raw water, pure water and feed water of the thermal power plant were investigated. The results of this study allow to explore ways of economical and effective descaling formed in heat exchangers
Keywords: thermal power plant; flow rate; pressure; temperature; scale; reagents; coagulants; elements; filtration; cleaning; washing